ANALYSIS OF INTERNAL CONTROL SYSTEM IN REVENUE CYCLE (A Case Study in Sahid Montana Dua Hotel) - Monica Audrey Jaya Suwana; Ali Djamhuri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
Hotel income is not only obtained from a single source, therefore there is a need of management tool that can control and monitor income regularly from each income source. To give optimal contribution for the management, it is necessary to have an appropriate internal control system and good accounting control system so that the demand for relevant information by management can be fulfilled. This research employs descriptive qualitative approach. This approach is intended to provide a description about the research object which is internal control system in revenue cycle at Sahid Montana Dua Hotel. The data are obtained through observation, interviews, and documentation.Next, the phenomenafound are analyzed based on its individual component as set by the Committee of Sponsoring Organizations of the Treadway Commission (COSO) and evaluated to give some suggestions that can be useful for company and management. Based on the results of the evaluation, Sahid Montana Dua Hotel has a good internal control system in revenue cycle. However, there are some problems found because of the double duties in some positions that can lead to lack of control. In addition, the existing organizational structure has to be revised because it doesn’t describe the real condition/structure. Some improvements have to be made in the aspect of reporting procedures, organization structure and monitoring, so that the hotel internal control system can be more effective. Keywords: Accounting Information System, Internal Control System, Revenue cycle